All for one and one for green energy: Community renewable investments in Europe - Valeriya Azarova; Jed Cohen; Andrea Kollmann; Johannes Reichl (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
A crucial part of the recently adopted "Fit for 55" package of the European Commission is devoted to the transition to a greener energy system. More specifically, the amendment to the Renewable Energy Directive sets up an increased target to produce 40% of energy from renewable sources by 2030. Hence, encouraging private investments in renewable generation capacity is becoming even more imperative to reach the ambitious climate-neutrality goals of the EU and to make the European Green Deal a reality. In this context, a pertinent design and endorsement of community renewable energy (CRE) projects may play a crucial role. A recent study based on a survey administered across 31 European nations, shows that there is high interest across Europe in CRE investment models, with 79% of respondents choosing to invest in at least one of the eight investment scenarios shown to them. Yet, operational details matter: e.g. administration through a local community organization is preferred to being administrated by an utility company. On top of that, highlighting local economic benefits, such as job creation from CRE projects, improves participation more so than highlighting general environmental benefits.
Keywords: 330